History, Film Historian, and Inventing of Captive Archives. An Interview with Michèle Lagny - Szczepanik, Petr (Iluminace, 2004)
An interview with Professor Michèle Pauline Lagny, who teaches film and cultural history at the University of Paris and leads research projects on film and cinema from a historical perspective.
Keywords: French film historian; historical research